2007
DOI: 10.1897/06-481r.1
|View full text |Cite
|
Sign up to set email alerts
|

A lateral flow immunoassay for rapid evaluation of vitellogenin levels in plasma and surface mucus of the copper redhorse (Moxostoma hubbsi)

Abstract: Abstract-We tested a lateral flow immunoassay (LFIA) for detecting vitellogenin (VTG) in plasma and surface mucus of copper redhorse, Moxostoma hubbsi, a threatened fish species. The LFIA detected VTG in samples from estradiol-induced fish, though there was no reaction in samples from noninduced individuals. The minimum detection range was 0.08 to 0.60 g VTG/ml, comparable to other methods. The LFIA has the potential to detect exposure to estrogenic endocrine-disrupting chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…7), as previously shown by Maltais and Roy (2007) for copper redhorse VTG. Samples of plasma and surface mucus extracts from E2B-induced shorthead redhorse were also subjected to reducing SDS-PAGE and Western blot with the anti-carp VTG as primary antibody.…”
Section: Amino Acid Analysissupporting
confidence: 78%
See 4 more Smart Citations
“…7), as previously shown by Maltais and Roy (2007) for copper redhorse VTG. Samples of plasma and surface mucus extracts from E2B-induced shorthead redhorse were also subjected to reducing SDS-PAGE and Western blot with the anti-carp VTG as primary antibody.…”
Section: Amino Acid Analysissupporting
confidence: 78%
“…In a previous study, we demonstrated that commercially available anti-carp VTG antibodies could be used to measure VTG in plasma and surface mucus of copper redhorse (Maltais and Roy 2007). In this study, we describe the purification and partial characterization of VTGs from both redhorse species and show antigenic cross-reactivity of the anti-carp VTG with plasma and mucus from the shorthead redhorse.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations